Effects of Team Emotional Authenticity on Virtual Team Performance - Connelly, Catherine E.; Turel, Ofir (Frontiers in Psychology, 2016)
Members of virtual teams lack many of the visual or auditory cues that are usually used as the basis for impressions about fellow team members. We focus on the effects of the impressions formed in this context, and use social exchange theory to understand how these impressions affect team performance. Our pilot study, using content analysis (n = 191 students), suggested that most individuals believe that they can assess others’ emotional authenticity in online settings by focusing on the content and tone of the messages. Our quantitative study examined the effects of these assessments. Structural equation modeling (SEM) analysis (n = 81 student teams) suggested that team-level trust and teamwork behaviors mediate the relationship between team emotional authenticity and team performance, and illuminate the importance of team emotional authenticity for team processes and outcomes.